The correlation of cough medicine advertisement in television on community self-medication in Krajan Sae Beji Village Junjero Batu City (Based on BPOM Head Regulation Number 8 in 2017) - Mutiara Titani; Rahmat Hidayat; Ika Ratna Hidayati (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2019)
Self-medication is an action treat by taking its own actions from assessing complaints and symptoms and drug selection. In doing self-medication, the community must have knowledge of the symptoms and drugs obtained from several sources, for example in television advertising. So this research’s goals is to determine the relationship of cough medicine advertisements on television to self-medication attitudes in Krajan Sae Hamlet, Beji Village, Junrejo Subdistrict, Batu City. This research is a descriptive study with  quantitative approach. Using instrument validated questionnaires. The sampling technique used is incidental sampling. The number of samples used refers to the Slovin’s formula with 97 respondents. To process this research the researcher use SPSS and Ms. Excel to get the correlation between cough medicine advertisements on television with public self-medication actions, influential indicators and linear regression results. The indicator that give influence of self-medication is indicator that is not misleading because it has the largest t count value of 2,360 with t table value 1,988 (df = 95). Regression  obtained by the results of simple linear regression equations namely Y = 7.618 + 0.303x. It means that, self-medication for cough medicines advertised on television will increase by 0.303 (b) units for each addition of one drug  unit. The results of the correlation study were analyzed using Ms. Excel obtained the results of r count 0.298 (N = 97, alpha = 0.05), with r table 0.195 (N = 100, alpha = 0.05). So that the value of r count > r table so Ho is rejected and Ha is accepted. It can be concluded that there is a relationship between cough medicine self-medication and television cough drug advertisement in Krajan Sae Hamlet, Beji Village, Junrejo Subdistrict, Batu City.